PERANCANGAN DATA FLOW DIAGRAM UNTUK SISTEM INFORMASI SEKOLAH (STUDI KASUS PADA SMA PEMBANGUNAN LABORATORIUM UNP) - Rita Afyenni (Jurnal Teknoif Teknik Informatika Institut Teknologi Padang, 2014)
Data Flow Diagrams (DFD) is a tool that can be used to describe the system designed. DFD depictions preceded by Context Diagrams (CD). CD uses three symbols, namely: external entity, a symbol to represent the flow of data and symbols to represent process. DFD using four symbols, namely: all symbols used on the CD plus one more symbol to represent the data store. DFD depiction is more focused on the process flow of data within the system that will make users better understand how data flows in the system and how the data is processed in the system. DFD is implemented at the school of information systems at the Laboratory of High School Development Padang State University (UNP Laboratory High School Building).